Pengaruh Kompensasi Dan Gaya kepemimpinan Terhadap Kinerja Karyawan Pada Bidang Parkir PT. Adhi Pratama Perkasa Palembang - Vivin Afini; Anton Trianto; Tutik Pebrianti; Imam Suroso; Aras Tulip (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2018)
This study aims to analyze the effect of compensation and leadership style on employee performance of Parking Division PT. Adhi Pratama Perkasa. By using saturated sampling method, the data taken is primary data obtained through a questionnaire instrument. The analytical tool uses multiple linear regressions. Calculation results show that Compensation variable (X1) and Leadership Style variable (X2) have significant effects on employee performance both partially and simultaneously.